Macrocell corrosion assessment of steel in cold-jointed concrete mixed and cured in seawater - Roxas, Cheryl Lyne C. (Animo Repository, 2018)
Previous research works have been devoted to developing sustainable construction materials. This is due to the potential risk of global warming resulting from the abuse and misuse of natural resources. Therefore, this study aims to address this through the use of abundant and by-product resources in the production of concrete, like seawater and fly ash. If these materials were proven comparable to conventional materials, then problems on freshwater scarcity, fluctuating supply of cement and associated pollutants from its production can be addressed. This research specifically concentrates on the effects of varying water to cement ratios and fly ash content on the macrocell corrosion behavior of steel in cold-jointed concrete. Ordinary Portland cement in concrete was partially replaced with fly ash at 30% and 50%. Water to cement (w/c) ratios of 0.30, 0.35, 0.40, 0.45, 0.55 and 0.60 were tested. Rectangular prism specimens were cast to monitor the macrocell corrosion activity of the reinforcements. Results have shown an increasing trend of corrosion rate with increasing w/c ratios regardless of mixing water, with specimens mixed with seawater having higher values compared to freshwater. Generally, the 0.30 w/c ratio resulted to the lowest corrosion susceptibility. In terms of fly ash content, it was found that corrosion rate decreases with increasing fly ash percentage. Fly ash decreases the permeability of concrete, thus making it less exposed to aggressive environments. Cold-joints showed evident corrosion effects as external elements may penetrate through these planes of weakness in the concrete. © Int. J. of GEOMATE.